Lithographically defined synthesis of transition metal dichalcogenides - Kemelbay, Aidar; Kuntubek, Aldiyar; Chang, Nicholas; Chen, Christopher T; Kastl, Christoph; Inglezakis, Vassilis J.; Tikhonov, Alexander; Schwartzberg, Adam M; Aloni, Shaul; Kuykendall, Tevye R. (IOP Publishing, 2019)
Transition metal dichalcogenides (TMDs) promise to revolutionize optoelectronic applications. While monolayer exfoliation and vapor phase growth produce extremely high quality 2D materials, direct fabrication at wafer scale remains a significant challenge. Here, we present a method that we call 'lateral conversion', which enables the synthesis of patterned TMD structures, with control over the thickness down to a few layers, at lithographically predefined locations. In this method, chemical conversion of a metal-oxide film to TMD layers proceeds by diffusion of precursor propagating laterally between silica layers, resulting in structures where delicate chalcogenide films are protected from contamination or oxidation. Lithographically patterned WS2 structures were synthesized by lateral conversion and analyzed in detail by hyperspectral Raman imaging, scanning electron microscopy and transmission electron microscopy. The rate of conversion was investigated as a function of time, temperature, and thickness of the converted film. In addition, the process was extended to grow patterned MoS2, WSe2, MoSe2 structures, and to demonstrate unique WS2/SiO2 multilayer structures. We believe this method will be applicable to a variety of additional chalcogenide materials, and enable their incorporation into novel architectures and devices.